1933 Cal. Stat. 1169 - (:unkn) unknown (My University, 1933)
Prohibited a person, firm, or corporation from selling, possessing or transporting a machine gun. Punishable by imprisonment up to 3 years and/or fine up to $5,000.
Keywords: MACHINE GUN RESTRICTION